2019
DOI: 10.1042/bsr20190267
|View full text |Cite
|
Sign up to set email alerts
|

JNK and cardiometabolic dysfunction

Abstract: Cardiometabolic syndrome (CMS) describes the cluster of metabolic and cardiovascular diseases that are generally characterized by impaired glucose tolerance, intra-abdominal adiposity, dyslipidemia, and hypertension. CMS currently affects more than 25% of the world’s population and the rates of diseases are rapidly rising. These CMS conditions represent critical risk factors for cardiovascular diseases including atherosclerosis, heart failure, myocardial infarction, and peripheral artery disease (PAD). Therefo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 126 publications
0
32
0
1
Order By: Relevance
“…Mitogen‐activated protein kinase 8 (MAPK8), also known as JNK1, belongs to JNK kinase family that consists of three members: JNK1, JNK2 and JNK3 . JNK directly binds and promotes phosphorylation of several transcription factors, such as NFAT, c‐Jun and JunB, and regulates multiple biological processes, including immune cell differentiation, inflammation, cancer progression and especially programmed cell death . JNK can trigger apoptosis, promote necroptosis, involve in non‐canonical pyroptotic signalling and induce autophagy by different molecular mechanisms .…”
Section: Discussionmentioning
confidence: 99%
“…Mitogen‐activated protein kinase 8 (MAPK8), also known as JNK1, belongs to JNK kinase family that consists of three members: JNK1, JNK2 and JNK3 . JNK directly binds and promotes phosphorylation of several transcription factors, such as NFAT, c‐Jun and JunB, and regulates multiple biological processes, including immune cell differentiation, inflammation, cancer progression and especially programmed cell death . JNK can trigger apoptosis, promote necroptosis, involve in non‐canonical pyroptotic signalling and induce autophagy by different molecular mechanisms .…”
Section: Discussionmentioning
confidence: 99%
“…Vascular diseases are related to changes in JNK expression 22 . Hui 51 showed that JNK plays a role in arteriosclerotic lesions.…”
Section: Discussionmentioning
confidence: 99%
“…The activation of cell signalling pathways is one of the most important mechanisms for understanding how tissues respond to different events that alter cellular homeostasis [21]. Numerous studies have demonstrated the importance of the c-Jun N-terminal kinase (JNK) pathway in these processes, as it responds to and regulates the pathophysiological changes that occur [22]. The importance of JNK dysregulation lies in the impact it has on gene expression, cell viability and the extracellular matrix, affecting the effectiveness of the tissues of the involved organ [23][24][25].…”
Section: Ivyspringmentioning
confidence: 99%
“…It is well known that the MAPK signalling pathway also plays an important role in the pathogenesis of hypertension-induced cardiac remodelling and heart failure [ 7 , 34 , 35 ]. MAP kinases, predominantly p38 MAPK and JNK, are other important regulators of myocardial fibrosis [ 24 , 36 , 37 ]. The activity of MAP kinases are regulated by dual-specificity phosphatases (DUSPs) or MAPK phosphatases (MKPs) that can dephosphorylate MAPKs and in this way regulate—actually inhibit—their activity [ 34 , 38 ].…”
Section: Discussionmentioning
confidence: 99%